Speech text of launching of International Certificate in Halal Supply Chain, awarding of the Halal Executive Certificate certified by JAKIM under the KPT-PACE programme and MoU signing between UiTM and HAL Fintech Advisor / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
Today we are going to witness the Launching of the International Certificate in Halal Supply Chain; the Awarding of the Halal Executive Certificate endorsed by JAKIM under the KPT–PACE programme to the graduating students of BBA (Transport) and BBA (Operations Management); and lastly, a Memorandum of Understanding(MoU)signing between Universiti Teknologi MARA and HAL Fintech Advisor(HFA).